Fighting for Resources: Using Data to Effectively Advocate for Your Department - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2023)
The Department chairperson is the primary spokesperson and advocate for the academic department. As many institutions continue to see enrollment declines and shrinking revenues, the ability for chairpersons to advocate effectively for limited resources has become even more important. Operating budgets, reassigned time, course offerings, and tenure-track faculty lines are all scrutinized with a focus on finding efficiencies. Today’s department chairperson must be adept at advocating for their department using data-based arguments. This session will review the most common data metrics used by deans to assess academic departments, and provide participants with clear, concise methods for using this data to effectively advocate for resources. Institutional teams are encouraged to attend together and begin to develop action plans for their respective units.
Keywords: Advocacy; Data; Leadership; Decision-Making; Administration